Efficacy and safety of conservative treatment for colonic diverticular bleeding: Prospective study - Doi, Hirosato; Takahashi, Masanori; Sasajima, Keita; Yoshii, Takehiro; Chinzei, Ryo (Endoscopy International Open, 2025)
This prospective study aimed to establish the efficacy and safety of conservative treatment for non-severe cases of colonic diverticular bleeding and to verify whether early colonoscopy is necessary only in limited cases.Patients who were urgently hospitalized due to hematochezia and were diagnosed with colonic diverticular bleeding were included. During hospitalization, early colonoscopy within 24 hours after admission was performed only when both systolic blood pressure < 90 mm Hg and extravasation on contrast-enhanced computed tomography were observed. However, in patients who failed to recover from hemorrhagic shock, interventional radiology was performed. In other cases, patients received conservative treatment.Of the 172 patients, 15 (8.7%) met the criteria for undergoing early colonoscopy; 12 and three attained successful hemostasis via early colonoscopy and interventional radiology, respectively. Meanwhile, 157 patients received conservative treatment, resulting in spontaneous hemostasis in 148 patients (94.3%). The remaining nine patients required hemostatic intervention. No patient died from bleeding. Between the conservative treatment and the urgent hemostasis groups, the early rebleeding rate within 30 days (14.6% vs. 33.3%, P = 0.0733) and the overall 1-year cumulative rebleeding rate after 30 days of hospitalization (9.2% vs. 23.1%, P = 0.2271) were not significant. In multivariate analyses, only systolic blood pressure and extravasation were associated with a requirement for hemostatic intervention in 24 patients. Moreover, multivariate analyses showed that a history of diverticular bleeding, undergoing hemodialysis, or use of oral thienopyridine were significantly associated with late rebleeding.Conservative treatment for non-severe colonic diverticular bleeding is appropriate and efficient.
Keywords: Endoscopy Lower GI Tract; Lower GI bleeding; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...)